Ulil Abshar Abdalla's Criticism of the Caliphate Concept of Hizbut Tahrir in Indonesia - Muhammad Rizky Silaban (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The polemic in discussing the concept of the caliphate has always been a never-ending debate. The Hizbut Tahrir Indonesia group is one of the leading forces that continuously promotes the caliphate, a system that some Islamic groups claim is the only solution to the problem of civilization, in which Muslim society is considered the main force in the glorious history of Islam. This qualitative literature study discusses the discourse of thought and criticism of understanding the Khilāfah a la Hizbut Tahrir concept. This study shows Ulil Abshar Abdalla's criticism of Hizbut Tahrir Indonesia's interpretation of leaders who must take conventional actions or allegiance; according to him, matters that are no longer relevant because matters of leadership are not regulated in detail in religion but social laws that apply depending on the conditions of society. Hizbut Tahrir Indonesia's understanding is a bad idea because it is considered an act of manipulating arguments and claims on things considered wrong. Their concept has a bad influence, triggering a wider internal conflict and the decline of the people, on the other hand. Islam does not want the existence of a state because, basically, Islam only regulates fundamental values in society.